ANCIENT METALLURGY IN THE BULGARIAN LANDS: ANCIENT METALLURGY IN THE BULGARIAN LANDS - Doncheva, Stella (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Ancient metallurgy is a broad concept and is associated both with mining and metalworking, and in many cases is evidence of their existence. Data on metalworking are indirect evidence of the development of mining. Metal implements, weapons, and ornaments were the most mobile material, and metal and its articles were one of the main objects of ancient barter. The development of metallurgy became one of the main drivers of economic life during different historical eras, and the territory of Bulgaria is no exception, but on the contrary, it is one of the places where this activity originated and developed for centuries.